Kandungan Nitrat Di Perairan Pasir Putih, Kecamatan Bungatan, Kabupaten Situbondo - Anita Diah Pahlewi; Wazirotus Sakinah (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
The biological, chemical and physical compounds in waters will effect the life of the biota in it. Nitrate is the main form of nitrogen in natural waters and the major nutrient for alga growth. The aim of this research is determining the concentration of nitrate in Pasir Putih waters, so that the research data can be utilized as water quality monitoring in Pasir Putih waters, Bungatan district, Situbondo regency. The nitrate data in marine waters sampling was collected from three stations and through laboratory analysis methods. The marine waters samples ware putted in dark glass bottles and stored in coolbox for aboratory analysis, then the data results was compared with water quality standard based on theDecree of the State Minister of the Environment Number 51 of 2004. The average of the concentration of nitrate at station A is 6,8 mg/l; at station B is 10,2 mg/l; at station C is 5,6 mg/l. The average of nitrate concentration at sampling stationsis 7,53 mg/L shows that nitrate concentration level is exceed the water quality standard based on the Decree of the State Minister of the Environment Number 51 of 2004. This leads to an indication of anthropogenic pollution in the waters due to the existence of floating net cages near the research location at Pasir Putih waters Situbondo regency. It needs further researchs about the presence of floating net cages to the surrounding water quality.